Rethinking the aesthetic design of school space. An "infinite question" with echo in teacher professional development (Praxis Educativa, 2021)
What do school spaces reveal about our image of childhood and education? Early Childhood Education classrooms often present an anachronistic and infantilized aesthetics that reflects the image that teachers have about children’s capacities. This article intends to open ways for the consideration of the space beauty as a variable that conditions the educational process and, specifically, the reconstruction of the practical knowledge of the teachers who are in charge of its design. For this purpose, a case study is presented which aims to understand the experience of reflection and pedagogical, spatial and personal transformation lived by a group of Early Childhood Education teachers from a public center in Malaga (Spain). The results indicate the potentiality of this reflection and methodological-spatial transformation for the questioning of the teaching ideas and actions, reinforcing practices that are more consistent with their theoretical principles.